Task-based cycle in reading comprehension classes. - Nahavandi, Naemeh; Mukundan, Jayakaran (Australian International Academic Centre, 2013)

(untitled)
This study has investigated the effect of task-based cycle on Iranian Elementary EFL learners' reading comprehension.In order to accomplish the research, two intact classes, including 84 engineering EFL learners (studying pre-universitycourse) were chosen in Tabriz Azad University. An experimental method of research was employed. The experimentalgroup was taught according to the elements of task-based cycle proposed by Willis & Willis, (2007). The control groupdidn’t receive such treatment. After eight sessions (3 months), a post-test was given. The analysis of the obtained data,carried out through t-test, revealed a significant difference between control and experimental group on the dependentvariable, reading comprehension. However, gender didn’t affect reading comprehension significantly. The results of the present study may have pedagogical implications for instruction and curriculum development.